Cadmium exposure inhibits MMP2 and MMP9 activities in the prostate and testis - Lacorte, Livia Maria [UNESP]; Rinaldi, Jaqueline de Carvalho [UNESP]; Justulin Junior, Luis Antônio [UNESP]; Delella, Flavia Karina [UNESP]; Moroz, Andrei [UNESP]; Felisbino, Sérgio Luis [UNESP] (Elsevier B.V., 2015)
Matrix metalloproteinases (MMPs) are zinc (Zn2+) and calcium (Ca2+) dependant endopeptidases, capable of degradation of numerous components of the extracellular matrix. Cadmium (Cd2+) is a well known environmental contaminant which could impair the activity of MMPs. In this sense, this study was conducted to evaluate if Cd2+ intake inhibits these endopeptidases activities at the rat prostate and testicles and if it directly inhibits the activity of MMP2 and MMP9 at gelatinolytic assays when present in the incubation buffer. To investigate this hypothesis, Wistar rats (5 weeks old), were given tap water (untreated, n = 9), or 15 ppm CdCl2 diluted in drinking water, during 10 weeks (n = 9) and 20 weeks (n = 9). The animals were euthanized and their ventral prostate, dorsal prostate, and testicles were removed. These tissue samples were processed for protein extraction and subjected to gelatin zymography evaluation. Additionally, we performed an experiment of gelatin zymography in which 5 mu M or 2 mM cadmium chloride (CdCl2) was directly dissolved at the incubation buffer, using the prostatic tissue samples from untreated animals that exhibited the highest MMP2 and MMP9 activities in the previous experiment. We have found that CdCl2 intake in the drinking water led to the inhibition of 35% and 30% of MMP2 and MMP9 (p < 0.05) at the ventral prostate and testis, respectively, in Cd2+ treated animals when compared to controls. Moreover, the activities of the referred enzymes were 80% and 100% inhibited by 5 mu M and 2 mM of CdCl2, respectively, even in the presence of 10 mM of CaCl2 within the incubation buffer solution. These important findings demonstrate that environmental cadmium contamination may deregulate the natural balance in the extracellular matrix turnover, through MMPs downregulation, which could contribute to the toxic effects observed in prostatic and testicular tissue after its exposure.
Keywords: Prostate; Cadmium; Matrix metalloproteinases; MMP2; MMP9; Zymography